Does listening to audiobooks affect gait behavior? - Aisuluu Atakanova; Thea Laurentius; Cornelius Bollheimer; Frank Hildebrand; Hannah Lena Siebers (BMC Sports Science, Medicine and Rehabilitation, 2023)
Abstract Background The effect of listening to audiobooks, podcasts, and other audio files while walking on gait performance has not been well studied. Although the number of audio users is growing annually. Evidence suggests that a posture-first strategy contributes to gait stability in healthy individuals during dual-task conditions, but this effect may be diminished when the cognitive task is consciously prioritized. Objectives: To study the effect of listening to an audiobook while walking, as a daily life-like dual-task, on spatiotemporal gait parameters. Methods Forty young healthy (24.05 ± 3.66) subjects participated in the study. Spatiotemporal gait parameters were measured for 5 min on a treadmill once without (single-task) and once while listening to an audiobook through over-ear headphones (dual-task). Measured parameters included spatiotemporal parameters, gait phases, maximum pressure, and dual-task cost. Data were statistically analyzed using SPSS software. Results There were no significant differences in any of the studied parameters between the single- and dual-task conditions, even though the subjective cognitive load of listening to audiobooks while walking was high. However, participants with different habits had significant differences in gait phases and maximum pressure. Rare listeners had a shorter stance phase, a longer swing phase, and a higher maximum pressure on the dominant heel. They also had significant differences in dual-task costs. Conclusion No differences in the spatiotemporal gait parameters for walking with and without listening to audiobooks, as a daily life-like dual-task, were observed. However, the difference between participants who listened rarely and participants who listened often may confirm the “posture first” strategy in young healthy people. Trial registration DRKS00025837, retrospectively registered on 23.11.2021.